The Impact of Grain Type and Sieve Holes on some Hammer Mill Performance Measures - Kakahy, Amer N. N.; Mohammad, Omar H.; Ahmed, Hawri S.; Kakei, Ayad A.; Alhamdany, Heba M. M.; Kakiy, Lazgin H.; Abdullah, Mariya M.; Sidiq, Rawezh D.; Faeq, Mahmood S (American Journal of Botany and Bioengineering, 2026)
This paper examines the impact of various grain type (wheat and barley) and sieve hole size (1.5, 2.5 and 3.5 mm) on the productivity of agricultural hammer mills and the physical quality of the milled produce. The paper particularly investigated how these operating parameters influence the milling assessment parameter, geometric mean diameter, specific capacity, and specific energy consumption. Increased diameters of sieve holes were observed to have significant relations with increased specific capacity and geometric mean diameter, whereas specific energy consumption and the milling evaluation factor declined. In particular, doubling the sieve size to 3.5 mm doubled the specific capacity (up to 680.0 kg.h-1) of wheat and reduced barley, and cut energy requirements by a significant margin. Compared to barley which produced a better milling evaluation factor and finer particle properties (averaging 0.55 mm at 1.5 mm sieve size), wheat was able to continuously produce higher specific capacities and lower specific energy consumption, falling to 7.8 kWh.t-1. Finally, 3.5 mm sieve holes with wheat yield the highest throughput and energy efficiency and 1.5 mm sieve holes with barley the highest milling evaluation factor (0.94) and particle uniformity. This shows that the optimum milling environment hinges on the targeted nutritional and physical production specifications that are sought by particular livestock feeds.